2017
DOI: 10.1007/s00737-017-0779-9
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral, cognitive, and emotional coping strategies of women with endometriosis: a critical narrative review

Abstract: Endometriosis is a disabling and long-term medical condition affecting quality of life and mental health. Behavioral, cognitive, and emotional coping strategies, emotional intelligence, and metacognition could in part explain the link between the disease and impaired psychological and life functioning. This critical narrative review aimed at examining the state of the art of the relationships between endometriosis and these factors. According to PRISMA principles, we performed a systematic search for quantitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(38 citation statements)
references
References 54 publications
5
33
0
Order By: Relevance
“…Women's accounts did not support work by Altinbas et al (2015) who suggested that pain caused by endometriosis does not affect quality of women's lives; on the contrary, women's accounts showed that dealing with chronic pain was a constant struggle, and pain and fatigue impacted on women's lives on a day to day basis. Results support data from reviews by Young et al (2015) and Zarbo et al (2018) which showed that pain is the key negative experience reported by women with endometriosis. This pain and associated fatigue impacted on all domains of life, including employment and social life, supporting Facchin et al's (2015) suggestion that endometriosis with pelvic pain causes significant negative impacts on quality of life in women experiencing these symptoms.…”
Section: Links To Previous Worksupporting
confidence: 81%
“…Women's accounts did not support work by Altinbas et al (2015) who suggested that pain caused by endometriosis does not affect quality of women's lives; on the contrary, women's accounts showed that dealing with chronic pain was a constant struggle, and pain and fatigue impacted on women's lives on a day to day basis. Results support data from reviews by Young et al (2015) and Zarbo et al (2018) which showed that pain is the key negative experience reported by women with endometriosis. This pain and associated fatigue impacted on all domains of life, including employment and social life, supporting Facchin et al's (2015) suggestion that endometriosis with pelvic pain causes significant negative impacts on quality of life in women experiencing these symptoms.…”
Section: Links To Previous Worksupporting
confidence: 81%
“…A possible explanation for our results is that the older women might have developed coping mechanisms over time that could decrease the impact of the symptoms. This has also been suggested earlier [19,20].…”
Section: Discussionsupporting
confidence: 83%
“…We believe that supporting women's abilities to cope with endometriosis and enabling integration of life and disease, based on personal values and preferences, remain key tasks for nurses. Positive coping strategies focusing on the problem or on emotions in relation to endometriosis were in a recent review found to be associated with better mental health (40).…”
Section: Discussionmentioning
confidence: 99%